Changes in skeletal muscle architecture following a cycloergometer test to exhaustion in athletes - Brancaccio, P.; Limongelli, F. M.; D`Aponte, A.; Narici, M.; Maffulli, N. (Journal of Science and Medicine in Sport, 2008)
We determined whether a short-term exhaustive dynamic exercise (cycling) for about 18 min induces changes in the intramuscular architecture of the quadriceps in trained athletes. Thirty-five male athletes (age 28.8 ± 9.8 years; height: 175.4. ± 5.5 cm; weight: 74 ± 11.5 kg; average years spent training: 11.1 ± 8.4 years; mean weekly duration of training: 10.4 ± 3.20 h) underwent an incremental cycloergometer test to exhaustion. Muscle thickness of the right quadriceps femoris (rectus femoris + vastus intermedius), and the angle of pennation of the right vastus lateralis on the quadriceps tendon were determined by high-resolution real time ultrasonography. Quadriceps thickness increased from 32.1 ± 3.3 mm at rest to 34.9 ± 3.0 mm after the test (p = 0.001). The pennation angles were significantly greater after exercise (12.8 ± 2.1° at rest; 14.4 ± 2.5° after the test (p = 0.001)). There are marked changes in intramuscular architecture of the quadriceps following a bout of cycloergometer exercise to exhaustion, with significant increase of quadriceps thickness and pennation angle. Ultrasonography allows to evaluate the changes of muscle architecture following exercise.